2021
DOI: 10.3390/su132011315
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Policy Measures in Reducing the COVID-19 Pandemic: A Case Study of South Asia

Abstract: The COVID-19 pandemic is considered to be the world’s most urgent health disaster and the greatest challenge humanity has faced since World War II. One of the most significant concerns is the effectiveness of the extraordinary efforts undertaken around the world to prevent the spread of the coronavirus. This study applied the Westerlund cointegration test and the Pooled Mean Group–Autoregressive Distributed Lag (PMG-ARDL) model to investigate the effectiveness of government policy measures in reducing the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Stringency policies also have a negative and significant effect on the number of new cases. This confirms the findings of the extensive literature on the impact of containment and mobility restriction policies (Brauner et al, 2021 ; Chung et al, 2021 ; Fiore et al, 2021 ; Khan et al, 2021 ; Md Zamri et al, 2021 ; Pan et al, 2021 ; Violato et al, 2021 ). However, the effect of the stringency index becomes insignificant when the mobility/immobility variables are introduced, except in the case of the parks and workplace variables.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Stringency policies also have a negative and significant effect on the number of new cases. This confirms the findings of the extensive literature on the impact of containment and mobility restriction policies (Brauner et al, 2021 ; Chung et al, 2021 ; Fiore et al, 2021 ; Khan et al, 2021 ; Md Zamri et al, 2021 ; Pan et al, 2021 ; Violato et al, 2021 ). However, the effect of the stringency index becomes insignificant when the mobility/immobility variables are introduced, except in the case of the parks and workplace variables.…”
Section: Resultssupporting
confidence: 85%
“…mobility restriction policies (Brauner et al, 2021;Chung et al, 2021;Fiore et al, 2021;Khan et al, 2021;Md Zamri et al, 2021;Pan et al, 2021;Violato et al, 2021). However, the effect of the stringency index becomes insignificant when the mobility/immobility variables are introduced, except in the case of the parks and workplace variables.…”
Section: Modelling Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 42 ] also concluded that preventive health measures resulted in a stability in COVID-19 confirmed cases in Hong Kong. Government economic support for poor families, stringency, health and containment measures, must all be implemented during the pandemic to decrease the infection of COVID-19 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers found that in the COVID-19 era, green bonds were more successful than conventional bonds because of the increased transparency of interest rates and investment returns. During the COVID-19 pandemic, government initiatives radically affected global energy consumption patterns [18].…”
Section: Green Energy In the Asean Regionmentioning
confidence: 99%